The relationship between BMI and depression: a cross-sectional study - Cui, Hongyu; Xiong, Ying; Wang, Chengmin; Ye, Jiaming; Zhao, Weisen (Frontiers in Psychiatry, 2024)
Introduction Mental health problems, especially depressive symptoms, are becoming increasingly prominent, posing a significant risk to public health. Changes in the body mass index (BMI) may impact an individual’s mental health, however, the relationship between BMI and depressive symptoms is unclear. The purpose of this study was to investigate the association between BMI and depressive symptoms. Methods Using a multi-stage sampling method, 10,686 adults in Longgang District, Shenzhen City, Guangdong Province, China, were selected for participation in this study. Surveys were distributed in 2020 and 2021 to measure participant demographic data and health. Binary logistic regression, restricted cubic spline regression, and subgroup analyses were performed to explore the relationship between BMI and depressive symptoms. Results The results showed a U-shaped relationship between BMI and depression. Both obesity and underweight increased the risk of depression among the participants, especially in subgroups of participants who were young, highly educated, single and employed. Conclusion These findings suggest that adults should try to maintain a normal body weight as a way to prevent depression and maintain their physical and mental health.